Introduction to Light Emitting Diode Technology and Applications - Held, Gilbert (Auerbach Publications, 2016)
Recent improvements in LED technology have made them as ubiquitous as cell phones. In fact, LEDs light up almost all cell phones screens. The technology's myriad applications and low energy use have made it nearly impossible to get through daily chores without coming in contact with LEDs. Probable advances include increased ability of the technolog.